The characteristics and distribution of dentist workforce in Saudi Arabia: A descriptive cross-sectional study - Abdulaziz M. AlBaker; Yazed Sulaiman H. Al-Ruthia; Mohammed AlShehri; Samar Alshuwairikh (Elsevier, 2017)
Background: The Kingdom of Saudi Arabia has shown steady growth in the dental workforce over the last 20 years. Although the number of dental colleges has significantly increased in the last decade, there is not any study so far that described the status of the licensed dentist workforce in the kingdom. The present study aimed to explore the demographic distribution and professional characteristics of licensed dentist workforce in Saudi Arabia. Methods: This was a descriptive cross-sectional study using the Saudi Commission for Health Specialties (SCFHS) database to identify the number of licensed dentists in Saudi Arabia as well as their professional and demographic characteristics as of December 2016. The data was categorized based on gender, nationality, dental specialty, health sector, geographic location, and professional rank. Results: The number of licensed dentists working in the kingdom as of December 2016 was 16887 dentists, and the vast majority of them are professionally registered as general dentists (70.27%). The percentage of general dentists among the professionally registered female dentists is significantly higher than their male counterparts (79.71% vs. 64.80%; P < 0.001). Only 22.08% of the dentists working in the kingdom are Saudi. Most of the dentist workforce in the kingdom are male (61.06%). The mean age of the Saudi dentists is slightly but significantly younger than non-Saudi dentists (37.7 vs. 40.7 years; P < 0.001). Over 80% of the Saudi dentists are working in the regions of Riyadh, Makkah, and Eastern province. About 66% of the Saudi dentists are working in the public health sector in comparison to only 20.46% of the non-Saudi dentists (P < 0.001). Conclusions: Most of the dental care in Saudi Arabia is provided by non-Saudi dentists in both private and public health sectors. With the rising unemployment rate among Saudi dentists, the governmental bodies that are responsible of dental labor market regulations such as the ministries of health, economy and planning, and labor should come up with a policy to gradually but carefully replace the non-Saudi dentists in both public and private sectors with Saudi dentists. Keywords: Dental workforce, Dentists-to-population ratio, Oral health, Saudi Arabia, Dentists